Military expenditure and economic development in China: an empirical inquiry - Fumitaka Furuoka; Mikio Oishi; Mohd Aminul Karim (Taylor & Francis Group, 2016)
Increases in military spending have a big impact on the socioeconomic conditions in any country. However, there is no consensus as to whether the rising military expenditure is beneficial or detrimental to economic growth. The present study chose China as a case study to empirically examine a complex relationship between military expenditure and economic development. The findings from the Johansen cointegration test indicated that there existed a long-run relationship between China’s military spending and economic growth. Furthermore, the Granger causality test detected a unidirectional causality from economic development to military expenditure. These results were further confirmed by the findings from the impulse response function. This means that China represents an example of a developing economy where the size of military expenditure expands in the process of economic transformation.